Kesalahan Penerjemahan: Kategori dan Penyebab - Diana, Nirva; Hidayat, Agus; Meisuri (Kementerian Sekretariat Negara Republik Indonesia, 2022)
The process of converting words from one language to another is known as translation. It holds a considerable part in almost every element of human life. Considering its increasing importance, the quality of the translated result must be improved. In reality, translation errors are often committed by translators. This research aims to determine the types of errors and the causes. The researchers conducted content analysis research and evaluated various studies on translation errors and their causes to obtain the data. The researchers found that translators' primary types of errors are grammatical, lexical, syntactic, and faithfulness errors. The causes of errors that the researchers found are the translator's lack of understanding of the target language's structure. Besides, culturally-bound words contributed as one of the causes of a translation error. Keywords: translation, error types, and error causes